Formulation and Evaluation of Floating Capsules of Diltiazem Hydrochloride Prepared by Semisolid Matrix Filling Technology - Hemalatha, Prof. S. (Asian Journal of Pharmaceutics (AJP), 2018)
Objective: The objective of this research work is to prepare and evaluate the sustained release semisolid matrix capsules of diltiazem hydrochloride (diltiazem HCl) developed using different grades of Gelucire in alone and in combination, to construct the calibration curve of diltiazem HCl in 0.1 N HCl, to prepare diltiazem HCl capsule using different Gelucire grades such as Gelucire 43/01, Gelucire 50/02, and Gelucire 50/13 and performing evaluation tests for all the prepared capsules (formulations). Materials and Methods: Various formulation of diltiazem HCl has been developed to reduce the frequency of dosing in chronic therapy. In the present study, the suitability of different grades of glycerides based excipients like Gelucires to formulate floating capsules by the method of semisolid matrix filling capsule technology. In the present research, different grades of Gelucires such as Gelucire 43/01, Gelucire 50/02, and Gelucire 50/13 were used to develop floating capsule of diltiazem HCl formulations developed and evaluated for the in vitro drug release and to evaluate gastric residence time by radiographic studies. Results: The in vitro drug release studies were conducted for all the formulations, that is, F1-F15 with 0.1 N HCl for 12 h. Among them, F10 showed 96.03 Â± 3.15 in a sustained manner and showed gastric residence time of about 6 h. Conclusion: In the present study, an attempt was made to formulate a sustained release formulation of diltiazem hydrochloride using different grades of Gelucires. The Gelucire grades having high lipophilicity could retard release rate than that of the grades with high hydrophilicity. Gelucire grades having hydrophilicity could enhance dissolution rate. The combination of both lipophilic and hydrophilic grades used for successful formulation of sustained release matrix capsules of diltiazem HCl.